Laparoscopic transabdominal preperitoneal herniorrhaphy performed using an articulating laparoscopic instrument is feasible and more efficient - Park, Jung Hyun; Kim, Dong Jin (Frontiers in Surgery, 2024)
Introduction Ipsilateral left-sided-approach laparoscopic transabdominal preperitoneal herniorrhaphy (LA-TAPP) is a procedure used for inguinal hernia. However, conventional laparoscopic instruments may limit the operator's ability to approach certain areas during the procedure. This study aims to assess the feasibility of using an articulating bipolar grasper (ArtiSential®). Material and Methods Between January 2017 and May 2022, 184 patients with inguinal hernia underwent LA-TAPP and were divided into an articulating group (AG) and a conventional group (CG). The two groups were compared for clinical characteristics, surgical outcomes, and recurrence rates. Learning curve analysis was also performed using the CUSUM score. Results The AG and CG included 72 and 112 patients, respectively. Both groups had similar age, sex, BMI, hernia location, and hernia type. The AG had a significantly shorter operation time (59.2 ± 29.4 vs. 77.8 ± 22.4 min, p < 0.001) than the CG. The duration of hospitalization was slightly shorter in the AG (2.2 ± 0.5 vs. 2.5 ± 1.4 days, p = 0.056). Postoperative complications were lower in the AG (5.6%) than in the CG (9.8%). Scrotal neuralgic pain was observed in 1.4% of patients in the AG and 3.6% of patients in the CG. Learning curve analysis revealed that 24 cases were needed to overcome the learning curve for using an articulating device. Conclusion IP-TAPP with an articulating instrument is a safe and efficient procedure. The operation time can be reduced by improving the surgeon’s procedural autonomy and reducing collisions between the instruments and the patient’s ribs.